Development of Website-Based Digital Mathematics Teaching Materials for Junior High School in the Era of Industrial Revolution 4.0 - Ranak Lince; Husnaeni Husnaeni; Rustam Rustam; Kusmaladewi Kusmaladewi (International Journal of Artificial Intelligence Research, 2022)
This research aims to develop website-based digital teaching materials for junior high school mathematics in the era of the Industrial Revolution 4.0. The current teaching materials are still manual although some are already in digital form. This type of research is development research or known as Research and Development (R & D). To achieve this goal, the process of developing this device will use the Plomp Development Model consisting of the preliminary investigation phase; design phase; realization/construction phase; test, evaluation and revision phase; and implementation. The implementation of this research was carried out at SMP Negeri 1 Barru, South Sulawesi Province. The validation results obtained are the level of media feasibility in terms of usability (82.5%); functionality (83.3%); and Visual Communication (73.3%) with an average feasibility level of 80% or in other words the feasibility level of this media is in the "FEASIBLE" category. The results of the media expert assessment show that SchooLearn in terms of all aspects can be declared valid, but there are still suggestions for improvement that need to be considered for the perfection of the developed device.